Smart and hyper-fast responsive polyprodrug nanoplatform for targeted cancer therapy. (January 2016) - Xu, Xiao-Ding; Cheng, Yin-Jia; Wu, Jun; Cheng, Hong; Cheng, Si-Xue; Zhuo, Ren-Xi; Zhang, Xian-Zheng
Abstract: The rapid development and clinical trials of biodegradable nanoparticles (NPs) are heavily hindered by many factors, including poor drug loading, low drug concentration at disease sites, lack of active targeting function, etc . Herein, we developed a new smart and hype-responsive polyprodrug platform with five key elements ( i.e . chemically incorporated drug molecules in backbone, stimuli-responsive bond, hyper-fast chain-breakage ability, hydrophilic segment and targeting ligand). Using 10-hydroxycamptothecin (HCPT) as model drug, we designed and prepared an exemplified redox-responsive amphiphilic polyprodrug via polycondensation and "click" chemistry. This polymer is composed of a hydrophobic HCPT-based polyprodrug, a hydrophilic poly(ethylene oxide) (PEG) chain and a tumor-targeting RGD tail. Employing nanoprecipitation technique, small-sized NPs (<70 nm) can be obtained. The in vitro and in vivo results prove that this newly developed nanoplatform has the following unique characteristics: 1) high and constant drug loading (>36 wt.%), 2) excellent tumor-targeting performance, 3) hyper-fast redox-responsive drug release (around 70% accumulative release within 2 h), 4) long blood circulation and 5) significant inhibition of tumor growth without side effects.